The Impact of Frame Running on Quality of Life in Young Athletes With Mobility Limitations - van Schie, Petra E. M.; van Eck, Mirjam; Bonouvrié, Laura A.; Edelman Bos, Arnoud M. M.; Buizer, Annemieke I. (Frontiers in Sports and Active Living, 2022)
Purpose The para-athletic sport Frame Running is developed for persons with neurological impairments causing severe limitations of walking ability. Participating in sports can contribute to a better quality of life (QoL). It is unknown if participation in Frame Running contributes to QoL in children with mobility limitations. This study aims to explore the changes in QoL in children and youth who started Frame Running. Materials and Methods We conducted a cross-sectional study amongst young Frame Running athletes with mobility limitations due to various underlying causes, aged 6–19 years, who are members of one of the Frame Running groups in the Netherlands. For 62 athletes, parents completed the Psychosocial Impact of Assistive Devices Scale (PIADS) questionnaire (subscales: competence, adaptability, and self-esteem). For six athletes, parents were interviewed to obtain more in-depth insight in the perceived changes in the QoL of their children. Results Parents (of 58% boys, mean age 12 years 4 months; SD 3 years 3 months; 52% supported walkers) reported a significant positive change on all three subscales of the PIADS questionnaire since their children started Frame Running. Most change was experienced in the items performance, the ability to participate, happiness and self-confidence. Quotes of the parents who were interviewed elucidated these changes. Conclusion Frame Running increased QoL in young athletes with a mobility limitation. Frame Running may therefore be advised for these children and youth to improve QoL.